(untitled) (Jurnal Peternakan Lingkungan Tropis, 2024)
This study aimed to analyze the differences between 2 feeds containing a combination of anti-oxidants P1 (monensin + diclazuril) and P2 (maduramycin + nicarbazine) on growth performance (feed consumption, PBB, FCR, mortality, and performance index) in starter phase broiler chickens. The analysis used in this research is the T-test (independent sample t-test) which consists of 2 treatments and 3 replications. The results showed that the administration of P1 had a significant effect (P<0.05) on all research variables. Based on the best average results occurred in P1, namely the administration of the anti-oxidant monensin + diclazuril which included the highest average feed consumption results of 1021.03 g/head/3 weeks, the highest average body weight gain of 822.30 g/head/3 weeks. The lowest average feed conversion ratio is 1.24, the lowest average mortality result is 1.04 and the highest average performance index value is 313.99. It is concluded that feeding a combination of the antioxidant monensin + diclazuril provided good performance in terms of feed consumption, body weight gain, feed conversion ratio, mortality, and performance index in starter-phase broiler chickens. This is an open-access article under the CC–BY-SA license.